Concomitant Medications and Risk of Chemotherapy‐Induced Peripheral Neuropathy. (23rd November 2018) - Sánchez‐Barroso, Lara; Apellaniz‐Ruiz, Maria; Gutiérrez‐Gutiérrez, Gerardo; Santos, María; Roldán‐Romero, Juan M.; Curras, Maria; Remacha, Laura; Calsina, Bruna; Calvo, Isabel; Sereno, María; Merino, María; García‐Donas, Jesús; et al.
Abstract: Background: Peripheral neuropathy is the dose‐limiting toxicity of many oncology drugs, including paclitaxel. There is large interindividual variability in the neuropathy, and several risk factors have been proposed; however, many have not been replicated. Here we present a comprehensive study aimed at identifying treatment and physiopathology‐related paclitaxel‐induced neuropathy risk factors in a large cohort of well‐characterized patients. Patients and Methods: Analyses included 503 patients with breast or ovarian cancer who received paclitaxel treatment. Paclitaxel dose modifications caused by the neuropathy were extracted from medical records and patients self‐reported neuropathy symptoms were collected. Multivariate logistic regression analyses were performed to identify concomitant medications and comorbidities associated with paclitaxel‐induced neuropathy. Results: Older patients had higher neuropathy: for each increase of 1 year of age, the risk of dose modifications and grade 3 neuropathy increased 4% and 5%, respectively. Cardiovascular drugs increased the risk of paclitaxel dose reductions (odds ratio [OR], 2.51; p = .006), with a stronger association for beta‐adrenergic antagonists. The total number of concomitant medications also showed an association with dose modifications (OR, 1.25; p = .012 for each concomitant drug increase). A dose modification predictive model that included the new identified factors gave an area under the curve of 0.74 ( p = 1.07 × 10 −10 ). Preexisting nerve compression syndromes seemed to increase neuropathy risk. Conclusion: Baseline characteristics of the patients, including age and concomitant medications, could be used to identify individuals at high risk of neuropathy, personalizing chemotherapy treatment and reducing the risk of severe neuropathy. Abstract : Peripheral neuropathy is a common adverse effect of many cancer drugs, including chemotherapeutics, targeted therapies, and immune checkpoint inhibitors. This article reports results of a study designed to identify treatment and physiopathology‐related paclitaxel‐inducd neuropathy risk factors in a cohort of ore than 500 patients.